Comparação de métodos para determinação da estabilidade de agregados por vias seca e úmida em diferentes sistemas de uso e manejo do solo - Perusi, Maria Cristina [UNESP]; Carvalho, Wolmar Apparecida (My University, 2008)
The purpose of the work is to evaluate the stability by dry and humid of theaggregate in different systems or the use and management in Argissolos: agricultural, pasture and torest utilization. This work was realized in agricultural property, in Anhumas city, SR Several analyses including percentage of the aggregate (by way of dry and humid); the weighted mean diameter of the aggregate calculation and statistic analysis. Conclusion: the organic matter content of the A horizon of the soil under forest is 64 % more than the soil under pasture and 79 % more than the soil under annual crop; the WMDA of the aggregate obtained by dry and humid ways of the horizon A and its mean value for the soil decrease in the following sequence: PVAd - forest > PVe -pasture > PVd - annual culture, respectively, with the following values: 1.33560 and 1.445496 (D), 2.81114 and 2.351380 (H); 0.66748 and 1.011830 (D); 2.79642 and 1.624250 (H); 0.32468 and 0.993775 (S), 1.25808 and 0.983135 mm (H); the two methods are equally sensitive to reveal the effect of the soil use and management; the organic matter provides additional stability to the aggregates submitted to humid sieving and clay to the dry sieving: the WMDA obtained by dry and humid ways are statistically different for the soil profiles.
Comparison of methods for the stability determination of the aggregate by dry and humid in the different systems of use and management of the soil
Keywords: Aggregates; Methods; Soil; Use and management; aggregate; comparative study; soil aggregate; soil management; soil organic matter; urban area; Brazil; South America